Simultaneous Estimation of Artemisinin and Dexamethasone in Nanodispersions and Assessment of Ex-vivo Corneal Transport Study by RP- HPLC - Ponnusamy, Chandrasekar; Krishnaswami, Venkateshwaran; Sugumaran, Abimanyu; Natesan, Subramanian (Current Pharmaceutical Analysis, 2014)
An improved RP- HPLC method with PDA detection has been developed and validated for the simultaneous estimation of artemisinin and dexamethasone in ocular nanodispersion formulations and it has been successfully adopted to check the ex-vivo corneal transport. The chromatographic separation was achieved using phenomenex C18 column (250 × 4.6 mm, 5 μm) analytical column and the mobile phase consisting of acetonitrile: (methanol : water, 4: 6) mixture at the ratio of 45: 55, v/v at a flow rate of 1.0 mL/min and injection volume of 200 μl. The column temperature was maintained at 50°C. The UV detection was carried out at 219 nm using photodiode array detector. The retention times of dexamethasone and artemisinin were found to be 4.5 and 7.9 minutes respectively. Artemisinin and dexamethasone calibration curves were found to be linear with correlation coefficient of 0.9617 and 0.9954 respectively at a dynamic concentration ranging from 250ng/mL to 1250 ng/mL. Recovery was between the ranges of 98.9% - 116.8% for both artemisinin and dexamethasone. The developed method is very selective as both peaks were well separated with a short analysis time of 10 minutes and does not require any preliminary treatment of sample.
Keywords: nanodispersions